The Research of the Effectiveness of the Program on Formation of Patriotic Qualities of Pupils - Kajumova, Diana F.; Khasanova, Oxana V.; Khripkova, Diana I.; Sadykova, Aida G.; Sharipova, Astrid V.; Vildanova, Elmira M.; Zaichenko, Marina A.; Ziatdinova, Julia N. (International Review of Management and Marketing, 2016)
The topicality of this problem is due to the contradiction between the objectively increasing requirements of society to a secondary school, Patriotic education of pupils and the lack of sufficient scientific and methodological bases of its organization in the activities of a teacher. In this regard, this article aims to develop a program on the formation of Patriotic qualities of pupils. Leading methods to the study of this problem were the observation, questionnaires, expert evaluation, self-assessment, identifying gaps in the formation of Patriotic qualities of pupils and to make timely correction. The article presents the program for the formation of Patriotic qualities of pupils, which allow to identify typical difficulties of teachers in the organization of this process, opened its structure and content, presents the results of the experiment for its implementation. The materials of this article, the positions contained therein and the conclusions can be used by teachers of schools, as well as in the system of teacher training. Keywords: Program, Pupils, Patriotic Education. JEL Classifications: A23, I23, I26